Analysis of the Effect of Break Even Points and Margins of Safety on Profit Planning in Hospitality Companies Listed on the IDX 2017-2021 - Arief Fadilah; Solihin Sidik (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2023)
Top management requires a plan to maximise revenues in order to succeed in a competitive business. The study's goal is to assess and evaluate the impact of the break-even point and the Margin of Safety on revenue and profit forecasts for hotel sub-sector IDX companies for the period of 2017 to 2021. Using the IDX and the company's own website, the researchers documented financial data gathered by researchers and given by firms operating in the hotel market. We performed multiple linear regression analyses with SPSS. Only two of the investigated hospitality-related businesses are found to be profitable (or at least break even), with the biggest safety margins. Profitability is heavily influenced by the break-even point as well as the margin of safety. The Break-even Point and the Margin of Safety have a very favourable effect for hotels listed on the IDX between 2017 and 2021.